“From Nail Bed to Nail Head”: An Unusual Case of Multiple Penetrating Nails over Head - Mishra, Sudhansu Sekhar; Behera, Bikash Ranjan; Das, Srikanta; Jena, Somnath Prasad; Rout, Sitansu Kumar (Indian Journal of Neurotrauma, 2015)
Multiple penetrating brain injuries are very common in military practice but not so common in civilian road traffic accidents. A rare case of penetrating head injury resulting from a road traffic accident has been presented. The 22-year-old man presented to us after encountering an accident in his maiden motorbike ride. In this accident he lost control of the bike and was catapulted of the bike unto a fence nearby. This fence had been constructed recently and had nails embedded in it. The result of this impact was this young man's skull being impregnated with three nails. With these nails he was retrieved from the site conscious, oriented, and was referred to our neurotrauma facility. On examination he had a GCS of E4V5M6, without any clinical features of raised intracranial pressure (ICP). The local examination suggested three iron nails in the right frontal region, which were firmly fixed to the underlying skull. The CT scan confirmed these clinical findings and an additional finding of a dural penetration and penetration of brain parenchyma. The patient underwent a prompt surgery, with the margin of the skin flap touching all the three nails and a craniectomy performed in a manner to aid the safe extraction of the nails and examination of underlying dura. The bone was discarded and the patient discharged uneventfully with advice of cranioplasty at a later date.
Keywords: penetrating head injury; nails; foreign bodies; craniectomy